Using a device for continuous infusion of a chemotherapeutic agent in the perception of the oncologic patient - Siqueira, Julianna de Freitas (2013)
This is a qualitative study whose aim was to describe the perception of an oncologic patient regarding the use of a device for continuous infusion of a chemotherapeutic agent. It was carried out with eight patients, through a semi-structured interview with this guiding question: “How do you feel about using a device for continuous infusion of a chemotherapeutic agent?”. Three categories emerged: avoiding hospitalization; unveiling the unknown; and performing activities. The patient highlights the benefit of going home and the possibility of performing activities, despite the anxiety regarding the presence of the device and the new experience in her/his daily life. The results were important to direct the guidelines related to the positive and negative aspects of this technology.